Landasan Teoritis Pembelajaran Bahasa Arab dalam Kajian Thuruq Tadris al-Lughah - Nabi Fikri Fuadi; Muhammad Hanif Athallah; Acep Hermawan; Eva Lathifah Fauzia (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to analyze the theoretical foundations of Arabic language learning within the framework of language teaching methods (Thuruq Tadris al-Lughah). The research employs a qualitative approach through library research, with data collected from relevant books and scholarly articles and analyzed using content analysis techniques. Through the processes of coding, categorizing, and synthesizing recurring themes across the selected literature, three major theoretical foundations of Arabic language learning were identified: philosophical, linguistic, and psychological. The philosophical foundation directs educational objectives toward the development of communicative competence as well as the cultivation of cultural and religious values. The linguistic foundation emphasizes the importance of understanding the phonological, morphological, and syntactic structures of the Arabic language. Meanwhile, the psychological foundation focuses on the application of learning theories, such as behaviorism, cognitivism, and constructivism, in the selection of instructional strategies. The study concludes that the integration of these three foundations contributes to the development of more effective and contextualized approaches to Arabic language teaching.